Primary fallopian tube carcinoma. Evaluation of clinicopathological prognostic factors in 21 cases - Bagul, Kiran; Rajanbabu, Anupama; Ranganathan, Venkatesan; Vijaykumar, Dehannathparambil Kottarathil; Jose, Amrutha; Nair, Indu; Pavithran, Keechilat (European Journal of Oncology and Environmental Health, 2017)
Objectives: Primary fallopian tube carcinoma (PFTC) is a rare cancer. Although comparable to epithelial ovarian cancer (EOC), PFTC may have different biology and prognosis than EOC. This single tertiary care hospital based study aims to evaluate the survival outcome and to identify factors that prognosticate the clinical outcome in PFTC patients. Methods: We retrospectively evaluated all the 21 patients diagnosed with PFTC between 2004-2013. We studied clinicopathological data to extract the prognostic factors for recurrence and survival. Kaplan-Meier curves were generated, and survival differences evaluated by using log-rank tests. Results: All the patients had pathologically proven PFTC. The mean age was 53.5 years (range: 36-69 years). Per-vaginal bleeding 11(52.2%) and abdominal pain 5 (23.8%) of average duration of 2.7 months were the commonest symptoms. Stage distribution at presentation, International Federation of Obstetrics and Gynecology (FIGO)-1991 stage I,II,III,IV were 33.3%, 19%, 42%, 4.7% respectively. Commonest histology was serous-papillary carcinoma 18 (86%).Optimal debulking was done in 18 (85.7%) cases. Seventeen (81%) patients received paclitaxol-carboplatin adjuvant chemotherapy. Median follow-up period was 31 months (range: 6-127months). The disease free interval was 23.5 months. Five year Overall survival was 42.8%. Lymphovascular space invasion was associated with advanced stage (p=0.026) and earlier recurrences (p=0.044). Factors prognostic for overall survival were FIGO stage (p=0.008) and lymph node metastasis (p=0.038). Conclusion: Our single institution study results show that presence of advanced stage at diagnosis and lymph nodal metastases results in poor overall survival. Presence of lymphovascular space invasion indicates increased recurrence risk. Future clinical studies are warranted to identify the possible distinct clinical behaviour of PFTC.